Pendampingan Kelompok Tani Hutan Desa Panglungan Dalam Pembibitan Porang (Amarphophallus onchophillus Prain) - Purwadi Purwadi; Purnomo Edi Sasongko; Ramdan Hidayat (LPPM Universitas Trunojoyo Madura, 2022)
Panglungan Village located in Wonosalam District, Jombang, with an altitude of 500 m above sea level, an area of 6.89 km2, and a population of 3,381 people. Most of the people's livelihoods rely on forest products such as coffee, durian, and avocado and a small portion come from dry land. The Panglungan Village community is part of the Forest Farmers Group (KTH) “U.D. Abadi Berkah Porang”, started to build porang nurseries, still on a household scale. The purpose of developing nurseries is to create alternative sources of livelihood that can be developed in the Panglungan Village area and its surroundings. Partner problems are 1). Farmers find it difficult to get porang seeds 2). Farmers' skills in Porang nurseries are still lacking 3). Quality porang seeds are not yet available, 4). The role of KTH “U.D. Abadi Berkah Porang” is not yet optimal. The solution to the problem is 1) Producing porang seedlings, 2). Assisting porang nurseries 3). Assistance with porang seed certification, 4). Empowering KTH